2012
DOI: 10.1016/j.lwt.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of malonylglucoside isoflavones in soybean flour analyzed by RPHPLC/DAD and eletrospray ionization mass spectrometry

Abstract: a b s t r a c tSoybean (Glycine max (Merrill) L.) contains high content of aglycone isoflavones, as well as glucoside and malonylconjugates. In this work, the content of isoflavones in defatted soy flour was determined by reversed-phase high-performance liquid chromatography (RPHPLC) after alcoholic extraction in methanol/water mixture in the ratio 80:20 (v/v). It was observed that the heating treatment transformed the malonylglucosides into glucoside isoflavones. After heat treatment at 121 C for 30 min, near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…In fact, industrial oil extraction includes thermal treatment that appears to play an important role in the isoflavone profile of defatted soy flour. Several studies have demonstrated that heat treatment of soybean flour promotes almost total conversion of malonylglycoside to β ‐glycosides without formation of acetylglycoside isoflavones, and this process is highly dependent on temperature . Thus, soy flour after industrial oil extraction should contain high levels of β ‐glycosides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, industrial oil extraction includes thermal treatment that appears to play an important role in the isoflavone profile of defatted soy flour. Several studies have demonstrated that heat treatment of soybean flour promotes almost total conversion of malonylglycoside to β ‐glycosides without formation of acetylglycoside isoflavones, and this process is highly dependent on temperature . Thus, soy flour after industrial oil extraction should contain high levels of β ‐glycosides.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that heat treatment of soybean flour promotes almost total conversion of malonylglycoside to -glycosides without formation of acetylglycoside isoflavones, and this process is highly dependent on temperature. 36 Thus, soy flour after industrial oil extraction should contain high levels of -glycosides. However, our results showed that aglycones are the major isoflavone group followed by -glycosides.…”
Section: Determination Of Total Phenolic Content and Compound Identifmentioning
confidence: 99%
“…The most frequently used solvent mixture for the extraction of the 12 major forms of isoflavones from soybeans and their derivatives is 80% aqueous methanol (Cavaliere and others ; Fiechter and others ; Hong and others ; Aguiar and others ; Gasparetto and others ; Fahmi and others ; Fonseca and others ; López‐Gutiérrez and others ; Verardo and others ). In very few cases pure methanol is used to carry out the extraction (Otieno and others ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…All soaking conditions promoted the reduction of malonyldaidzin, malonylgenistin, and malonylglycitin in soy protein concentrate when compared to control treatment (Table ). Malonylglucoside forms of isoflavones are sensitive and unstable with respect to thermal treatment being susceptible to both decarboxylation and de‐esterification reactions, forming the respective acetylglucosides and β‐glucosides, and after enzyme treatment they may be converted into aglycones (Aguiar et al, ; Park, Aguiar, Alencar, Mascarenhas, & Scamparini, ). The thermal instability of malonylglucosides was also observed during soybean soaking at different temperatures (41, 45, 55, 65, and 69°C) (Lima & Ida, ) and during soymilk processing at 40, 50, and 60°C (Baú & Ida, ).…”
Section: Resultsmentioning
confidence: 99%